2022
DOI: 10.1186/s41606-022-00080-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of sleep deprivation among Haramaya University students, Ethiopia, 2021: cross-sectional study

Abstract: Background Sleep deprivation is the lack of sleep that is associated with an increased risk of cardiovascular illness, diabetes, obesity, cognitive impairment, vehicle accidents, and workplace accidents, as well as being a direct source of daily dysfunction. Despite the fact that some studies have been undertaken, there is a shortage of data on the incidence of sleep deprivation and associated factors among university students in Africa, particularly in Ethiopia, where the study area is located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
1
Order By: Relevance
“…The prevalence of poor sleep quality found in this study is consistent with previous studies conducted in Ohio, USA (69.9% [ 34 ]) and Riyadh, Saudi Arabia (76% [ 35 ]). It was, however, higher than many previous studies conducted in Jimma, Ethiopia (65.4% [ 20 ]), Gondar (24% [ 36 ]) and Haramaya (68.4% [ 37 ]). In contrast, according to our assessment, no study report was higher than the current prevalence report.…”
Section: Discussioncontrasting
confidence: 61%
“…The prevalence of poor sleep quality found in this study is consistent with previous studies conducted in Ohio, USA (69.9% [ 34 ]) and Riyadh, Saudi Arabia (76% [ 35 ]). It was, however, higher than many previous studies conducted in Jimma, Ethiopia (65.4% [ 20 ]), Gondar (24% [ 36 ]) and Haramaya (68.4% [ 37 ]). In contrast, according to our assessment, no study report was higher than the current prevalence report.…”
Section: Discussioncontrasting
confidence: 61%
“…Although studies of sleep from African countries are more limited, recent studies suggest that insufficient sleep and poor sleep quality are also a problem across age groups. Recent studies highlight sleep deprivation in older adults and in university students (Lankrew Ayalew 2022; Nsengimana et al, 2023; Stranges et al, 2012; Wang et al, 2019). Despite the growing number of population studies on sleep and sleep disorders across multiple countries, the question of whether the incidence of sleep deprivation among individuals is increasing can be difficult to answer as many large‐scale studies rely upon self‐reported or subjective sleep tests, and the definitions of insufficient sleep can vary.…”
Section: Introductionmentioning
confidence: 99%